Research methodologies and methods in education - Arthur, James , 1957- (Sage Publications, 2012)
"This straightforward and jargon-free book will provide students with the theoretical understandings, practical knowledge and skills they need to carry out independent research. The international contributors identify key research methodologies, data collection tools and analysis methods and focus on the direct comparisons between them. Each chapter sets out the strengths and weaknesses of a key research method by: identifying specific research designs; presenting a series of relevant data collection tools; highlighting which analytical methods can be used. The chapters cover the full range of methods and methodologies, including internet research, mixed methods, and ethnographic research. Additional online materials are also available including links to useful journal articles. This is a key book for M-level students and other postgraduates within Education and Educational Research Methods courses."-- Cover p. [4].